(3efjI GdeUdjs - (3GdcGTZQj, SOjO GdOjf, eMeO Hf eMeO Hf Ydj, J (B705(3g`s
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf(B... (3GYde habc Gddg JYGdi hEjGfG Gf CfhGY GdYdhe cKjQI, hCge GdCfhGY HGdJMUjd eSGFd GdUdGI(B...s
(3BNQgG (B:s
(3hYGeI GdeTGjN Ydi Cf JQc GdeO hGdJTOjO HefRdI GdNWC(B... (3HGdJTOjO ajgeGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B7(3, U(B32s
(3cTa GdXfhf(B: (3L(B2(3, U(B1886s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis